2017
DOI: 10.4172/2161-0983.1000195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stable Isotope 13C6-glucose on Volatile Organic Compounds in Different Stages of Mediterranean Fruit Fly (Medfly) Ceratitis Capitata (Diptera: Tephritidae)

Abstract: The Mediterranean fruit fly (Medfly) Ceratitis capitata (Diptera: Tephidae), as most of the Tephritidae species, is a pest of great economic importance around the world. For Integrated Pest Management (IPM) and biological pest management purposes, this research will investigate characterization of the broadest possible range of volatile organic compounds and the possible changing trends of volatile biological emissions during development stages of insect. During the last years, many types of research have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Comparing the HS-SPME, compounds including: 2,3-hexanedione, o -dimethylbenzene, nonane, 2,3,4-trithiapentane, octanal, acetophenone, 2,6-dimethyl-( E , Z )-2,4,6-octatriene, 1H-pyrrole-2-carboxylic acid, 2,6,10-trimethyltridecane, dimethyl phthalate; farnesene, ( E )-γ-bisabolene, 5-phenyl- undecane, carboric acid 2-ethylhexyl octyl ester, 2-ethylhexyl octyl ester; and 5-dodecyldihydro-2(3 H )-furanone, were detected from medfly adults during mating stage ( Table 3 , Figure 4 ). Al-khshemawee et al [ 7 ] reported that the compounds acetoin, 2,3-hexanedione, hexaldehyde, 4-hydroxybutanoic acid, 2,3,4- trithiapentane and octanal were identified from medfly adults using HS-SPME. Jacobson et al [ 25 ] used HS-SPME to identify the pheromones from medfly adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the HS-SPME, compounds including: 2,3-hexanedione, o -dimethylbenzene, nonane, 2,3,4-trithiapentane, octanal, acetophenone, 2,6-dimethyl-( E , Z )-2,4,6-octatriene, 1H-pyrrole-2-carboxylic acid, 2,6,10-trimethyltridecane, dimethyl phthalate; farnesene, ( E )-γ-bisabolene, 5-phenyl- undecane, carboric acid 2-ethylhexyl octyl ester, 2-ethylhexyl octyl ester; and 5-dodecyldihydro-2(3 H )-furanone, were detected from medfly adults during mating stage ( Table 3 , Figure 4 ). Al-khshemawee et al [ 7 ] reported that the compounds acetoin, 2,3-hexanedione, hexaldehyde, 4-hydroxybutanoic acid, 2,3,4- trithiapentane and octanal were identified from medfly adults using HS-SPME. Jacobson et al [ 25 ] used HS-SPME to identify the pheromones from medfly adults.…”
Section: Resultsmentioning
confidence: 99%
“…In the first method, headspace SPME (HS-SPME), the polymeric film is exposed to the gas phase that adsorbs the volatiles in the headspace of the liquid, gas or gaseous samples. The second method is direct immersion (DI-SPME), in which the fiber is directly immersed in a small volume of the liquid-extracted sample [ 5 , 6 , 7 ]. After the sample matrix and SPME coating achieves equilibrium, the extracted SPME is inserted into a gas chromatograph-mass spectrometer (GC-MS) for thermal desorption or into a desorption solvent for coupling with liquid chromatography (LC-MS) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%